Dampak Lingkungan Sosial Ekonomi dalam Pembentukan Karir : Analisis Sesuai Teori Krumboltz - Annisa Zahrani; Aprilia Halimatul Jannah (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2024)
This research was conducted with the aim of knowing the impact of the socio-economic environment in career formation. The research method used is qualitative with a library research approach through descriptive analysis. The data collection technique used is a literature review in the form of books, journals, and articles that are in line with the issues raised in the study. The data analysis used was descriptive analysis based on literature data related to the research variables. The results of the review show that financial climate is significantly related to career arrangements. Families with good financial circumstances can offer greater assistance regarding access to education and career inspiration. On the other hand, financial barriers thwart such access, which is related to students' career decisions and development. . This study assumes that family financial circumstances, e.g., parents‘ education level, salary, and monetary power, are significantly related to students’ career planning and development.